The Effect of Polar Head and Chain Length on the Physicochemical Properties of Micellization and Adsorption of Amino Alcohol‐Based Surfactants. Issue 3 (20th December 2018) - Hafidi, Zakaria; El Achouri, Mohammed
Abstract : In this work, we have synthesized a series of quaternary ammonium from amino alcohols and n‐bromoalkanes. The compounds are referred to as Cn EtOH, Cn PrOH, and Cn iPrOH (where n = 12 and 14 carbons, EtOH = ethanol, PrOH = propanol, iPrOH = iso‐propanol). Their structures were checked using the usual spectroscopic methods [ 1 H, 13 C nuclear magnetic resonance (NMR) and infrared (IR)]. Their physicochemical properties in aqueous solution were studied using conductivity, surface tension, and ultra violet (UV)–visible absorption spectroscopy measurements. This study was conducted to show the effect of the linear hydrophobic chain and the location of the OH polar group with respect to the N + quaternary ammonium on the physicochemical properties of the surfactants. The comparison between the physicochemical properties of the surfactants studied shows a distinct effect of the position of the OH group on the critical micelle concentration (CMC), the ionization degree ( α ), the area occupied at the interface ( A min ), the free energy of adsorption ( Δ G ad 0 ), and the free energy of micellization ( Δ G M 0 ). The intermolecular interaction between the synthetic surfactants and the methyl orange (OM) dye is related to the degree of hydration of the micelle, proven by the hypsochromic displacement of OM wavelength ( λ max ) and ionization ( α ) of the micelles. The CMC, the degree of ionization, and the degree of hydration of the micelle follow the same trend.